The Effects of Health Insurance Coverage on the Math Achievement Trajectories of School Children in Yuma County, Arizona: Implications for Education Accountability Policy - Garcy, Anthony M. (Education Policy Analysis Archives, 2013)
U.S. Federal and state education policies place considerable emphasis on assessing the effects that schools and teachers have on student test score performance. It is important for education policy makers to also consider other factors that can affect student achievement. This study finds that an exogenous school factor, discontinuous health insurance coverage, leads to a deficit in math achievement over time. A sample of Yuma County, Arizona public school students who experienced an illness or injury and whose health insurance coverage status was known were selected for inclusion into the study over five consecutive school years (1999 – 2003). The longitudinal math achievement trajectory of students who had private health insurance coverage was compared to students who had discontinuous coverage. Net of a student’s poverty status and other background characteristics the findings suggest that students who experienced a health event when they had no healthcare insurance had the same growth rate but lower overall math achievement. The average achievement gap was a constant -8.84 scale score points. However, separate analyses for specific types of illness/injury suggest the achievement deficit varied considerably and is typically larger. Other important findings from the study suggest that students who maintained continuous health insurance coverage through the SCHIP/Medicaid program had steeper, positive achievement gains than either those with private coverage or those who experience coverage gaps.